Improvement in trading systems and management regulations to optimize the contributions of kemenyan to government revenues and farmers - Freddy Jontara Hutapea (Inovasi, 2022)
Kemenyan is a non-timber forest product that has high economic potential. Nevertheless, the economic benefits received by farmers and the government from kemenyan utilizations are still low. This study was aimed to describe various problems in kemenyan trading systems, calculate potential government revenues from kemenyan based on the existing regulations, and provide recommendations to improve kemenyan’s trading systems. The method used in this study was quantitative descriptive. The data on kemenyan forest area and kemenyan production were obtained from Central Bureau Statistics (BPS) and Plantation Statistics of North Sumatra Province. The results showed that in the last ten years, total kemenyan forests in North Sumatra Province decreased significantly, though they were not followed by the decrease in kemenyan production. Long kemenyan trading systems caused the utilization of kemenyan is less profitable to kemenyan farmers. Potential government revenues from kemenyan were about 10.18 billion rupiahs. Nonetheless, the contribution of kemenyan to government revenues was quite low as there was no implementation of Minister of Forestry Regulation Number P. 68 (2014) and Government Regulation Number 12 (2014). Improvements in kemenyan trading systems can be conducted through the establishment of regional-owned enterprises (BUMD) to cut the length of kemenyan trading systems. Local governments also need to produce a regional regulation as a basis for determining the contribution of kemenyan to government revenues. Kemenyan farmers also need to establish kemenyan farmer association, and actively participate in supporting government programs in improving kemenyan trading systems. Keywords: Kemenyan, economic potential, trading systems, government revenues, kemenyan farmers